University of the Philippines College of Dentistry position paper on amalgam.
Editor's Note: This article discusses the position of the University of the Philippines College of Dentistry regarding the continued use of dental amalgam as approved by the UPCD Faculty Council on September 2011. The opinions and stand in this article do not necessarily reflect the views and policies of the Philippine Dental Association, or The Journal.
Keywords: University of the Philippines. College of Dentistry; Dental amalgams